Tooth Cutting Machining of Cycloid Coupling based on Monolithic Cutter - Zhiyong Wang; Wenhao Yu; Ying Zhang; Yiyu Zeng (Jixie chuandong)
In order to realize the machining of the cycloid coupling on the domestic CNC bevel gear milling machine，the cutting principle and processing method of the cycloid coupling are studied. Based on the structural characteristics of the cycloid coupling，the processing method for machining cycloid coupling with monolithic cutter is proposed，and the lengthwise curvature and profile curvature are corrected by changing the radius of the cutter and the radius of the blade arc. Based on the cutting principle of cycloid coupling，the calculation method for the cutter parameters and the machine tool adjustment parameters for machining cycloid coupling is proposed. The cutter interference check is carried out on the cycloid coupling. Through the use of monolithic cutter to process the cycloid coupling on domestic CNC bevel gear cutting machine，the correctness and feasibility of cutting principle and processing method is verified by tooth profile error measurement and contact pattern inspection.